Multi-Window Setup for Thermomechanical Experiments Assisted by DIC up to 900°C - Rafael Vargas; Igor Paganotto Zago; Vinicius Fiocco Sciuti; Matheus Furlan; Ricardo Afonso Angélico; François Hild; Rodrigo Bresciani Canto (Materials Research, 2024)
Mechanical properties may drastically change with temperature, which is crucial to characterize materials in environments as similar as possible to their desired application. This paper discusses a new furnace designed for thermomechanical experiments assisted by Digital Image Correlation (DIC) up to 900°C, with six transparent windows that allow for the visualization and lighting of the specimen. Its versatility is demonstrated in three different experimental configurations, namely, dilatometry, three-point bend experiment, and wedge splitting test. Applied forces and full-field data are used for robust calibration of parameters for numerical simulations.